Best Answer

x3 - 7x2 + 6x

= x(x2 - 7x + 6)

= x(x2 - x - 6x + 6)

= x[x(x - 1) - 6(x - 1)]

= x2(x - 1) - 6x(x - 1)

= (x2 - 6x)(x - 1)

Q: What is the factorization of x3 -7x2 plus 6x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x3 - 7x2 + 6x =x (x2 - 7x + 6) =x (x - 6) (x - 1)

x3 + 4x2 + 6x + 24 = (x2 + 6)(x + 4)

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

(x + 5)(x^2 + 2x + 2)

x3 + 13x2 + 42x = x(x2 + 13x + 42) = x(x2 + 6x + 7x + 42) = x[x(x + 6) + 7(x + 6)] = x(x + 7)(x + 6)

Related questions

x3 - 7x2 + 6x =x (x2 - 7x + 6) =x (x - 6) (x - 1)

x3 + 4x2 + 6x + 24 = (x2 + 6)(x + 4)

x3 + x2 - 6x + 4 = (x - 1)(x2 + 2x - 4)

(x + 5)(x^2 + 2x + 2)

x3 + 13x2 + 42x = x(x2 + 13x + 42) = x(x2 + 6x + 7x + 42) = x[x(x + 6) + 7(x + 6)] = x(x + 7)(x + 6)

x3 + 13x2 + 42x = x(x + 6)(x + 7).

x3 + 3x2 - 6x - 8 = (x - 2)(x2 + 5x + 4) = (x - 2)(x + 1)(x + 4)

x3 - 10x2 + 24x = x(x2 - 10x + 24) = x(x2 - 4x - 6x + 24) = x[ x(x - 4) - 6(x - 4) ] = x(x - 6)(x - 4)

x3 + 2x2 - 35x = x(x + 7)(x - 5)

It is: (x2 + 5x) (x + 8)

x(x + 8)(x + 5)

x(x + 9)(x + 5)